Influence of Mycorrhiza on the plant growth and roots development of oil palm seedling / Siti Rahayu Muhamad Wahab - Muhamad Wahab, Siti Rahayu (Faculty of Plantation and Agrotechnology, 2015)
The experiment will be conduct under rain shelter of UiTM Jasin Campus with the controlled environment. The oil palm seedlings from (FELDA DXP) were purchased from Hong Seng Nursery as recommended by MPOB. Oil palm seedling in about 3 months old was chosen because an AM fungus is obligate microorganism that need host to perform. So that, 3 month old of oil palm seedling is chose with the present of their roots. Sources of the Mycorrhizal were product of Malaysian Agri Care (MyAgri) which is MYCOgold brand was used in this experiment. The treatments were done with 5 levels, including the control plant. They are inoculants with 0g, 20g, 30g, 40g and 50g of AM. The inoculations were done by inoculating different level of AM with soil before transplanting to the other polybag. The mixture of soil is based on the common soil mixture for planting oil palm. Every level of AM will be repeated 5 times and by using Complete Randomized Design (CRD).The result was obtained 3 month after the inoculation with AM. Observation is based on the diameter of trunk (1 month interval), number of fronds (1 month interval), and plant biomass which are the upper (leaves) and lower (roots) mass was weighed. The nutrients contained were measured by leaves analysis. The infections of the inoculation were observed under microscope. The results gained from this experiment are the positive infection of Mycorrhizal Fungi inoculation with the present of infection of the Mycorrhiza within the root cells of the oil palm seedling after 3 month application of Mycorrhizal Fungi and the optimum level of Mycorrhiza inoculation on oil palm seedling growth.